Analisis pengaruh Ukuran Perusahaan, Financial Stability dan External Pressure terhadap Earning Management dengan Financial Targets sebagai Variabel Moderasi - Rianto Rianto; Rina Rina (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2021)
This study aims to determine the effect of the influence of company size, financial stability, and external pressure on earning management with financial targets as a moderating variable (an empirical study of mining companies listed on the Indonesia Stock Exchange 2015 - 2018). Samples were taken using purposive sampling method with certain criteria during the study period. Based on the predetermined criteria and the use of panel data, the amount of data that can be processed is as many as 48 data. The data analysis method used is multiple linear regression which is processed using eviews9. The results of this study indicate that: (1) company size has a negative and significant effect on earning management (2) financial stability has a negative and significant effect on earning management. (3) external pressure has a positive and significant effect on earning management (4) company size cannot moderate the financial targets variable on earning management. (5) financial targets can moderate the financial stability variable against earning management. (6) financial targets can moderate the external pressure variable against earning management.